Non-linear analysis of wrinkling phenomena in sandwich beams with soft core - Jasion, Paweł; Wstawska, Iwona Małgorzata; Kołodziński, Kamil (Engineering Transactions, 2025)
The work is devoted to the local stability analysis of sandwich beams with light core. A linear as well as non-linear numerical analysis is carried out with the use of the finite element method (FEM). Both material and geometrical nonlinearities are taken into account. The goal of the investigation is to examine the influence of the material model on the post-buckling behaviour of a sandwich beam especially on the formation and developing of wrinkles on the compressed face. A pure bending condition is considered for the beam simply supported at both ends. The results for materials of theoretical properties are presented as well as for data from experiments on aluminium sandwich beams. From the results it is seen that the linear analysis of wrinkling phenomenon for non-linear materials gives overestimated results and does not predict correctly the buckling shape.